Assessing seasonal and diurnal thermal dynamics of water channel and highway bridges using unmanned aerial vehicle Thermography - Memduhoğlu, Abdulkadir; Polat, Nizar (Drones, 2025)
Bridges are critical components of modern infrastructure, yet their long-term performance is often compromised by thermal stresses induced by environmental and material factors. Despite advances in remote sensing, characterizing the complex thermal dynamics of bridge structures remains challenging. In this study, we investigate the seasonal and diurnal thermal behavior of two common bridge types—a water channel bridge with paving stone surfacing and a highway bridge with asphalt surfacing—using high-resolution UAV thermography. A pre-designed photogrammetric flight plan (yielding a ground sampling distance of <5 cm) was implemented to acquire thermal and visual imagery during four distinct temporal windows (winter morning, winter evening, summer morning, and summer evening). The methodology involved generating thermal orthophotos via structure-from-motion techniques, extracting systematic temperature measurements (n=150 per bridge), and analyzing these using independent-samples and paired t-tests to quantify material-specific thermal responses and environmental coupling effects. The results reveal that the water channel bridge exhibited significantly lower thermal variability (1.54-3.48 °C) compared to the highway bridge (3.27-5.66 °C), with pronounced differences during winter mornings (Cohen’s d=2.03, p<0.001). Furthermore, material properties strongly modulated thermal dynamics, as evidenced by the significant temperature differentials between the paving stone and asphalt surfaces, while ambient conditions further influence surface-ambient coupling (r=0.961 vs. 0.975). The results provide UAV-based quantitative metrics for bridge thermal assessment and empirical evidence to support the temporal monitoring of bridges with varying materials and environmental conditions for future studies.
Online veröffentlicht: 13. März 2025
Gesehen am 08.10.2025